On minimalism : documenting a musical movement - O'Brien, Kerry; Robin, William (Oakland, California : University of California Press, 2023)
"Minimalism changed everything. When composers like Philip Glass and Steve Reich began creating hypnotically repetitive music in the 1960s, it upended the world of American composition. Hip, young listeners flocked to a genre that had long been insular and academic, packing concert halls and buying millions of records. But minimalism wasn't just a classical phenomenon: its static harmonies and groovy pulses swept through the avant-garde landscape, shaping the work of experimental mavens Yoko Ono and Brian Eno, radical improvisers John and Alice Coltrane, outre innovators Pauline Oliveros and Julius Eastman, and many others. This book provides a comprehensive, revisionist retelling of minimalism's transformative rise, through the voices of the musicians who created it. Featuring more than a hundred rare historical sources, On Minimalism moves from the style's origins in psychedelic counterculture through its arrival in the mainstream and into its present-day manifestations in doom metal and ambient jazz. O'Brien and Robin curate minimalism's history anew, documenting one of the most important musical movements of our time"--
Foreword by Joan La Barbara -- Introduction -- Improvisation and Experimentation -- Dream Music -- Loops and Process -- Altered States -- Gurus and Teachers -- Cultural Fusion -- Across the Arts -- Ensembles -- 1976 -- The New Downtown -- Instruments and Environments -- Ambient Music and New Age -- Canons -- Backlash -- Politics, Identity, and Expression -- Postminimalists -- Spiritual Minimalism -- Popular Culture -- Histories -- Silences -- Futures.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: musiikki; minimalistinen musiikki; musiikinhistoria; taidemusiikki; populaarimusiikki; ambient; minimalismi; avantgarde; säveltäjät; muusikot; sävellykset; musik; minimalistisk musik; musikhistoria; konstmusik; populärmusik; ambient; minimalism; avantgarde; kompositörer; musiker; kompositioner